Visual Storytelling in the AI Era: A Study of the Uketsu Channel's Narrative Graphic Design on YouTube - Chandra, Edy (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Paramadina, 2025)
This study concludes that artificial intelligence (AI) plays a transformative role in enhancing visual storytelling on YouTube, particularly through the case of the Uketsu channel. The integration of AI-generated visual elements—such as atmospheric illustrations, narrative-driven diagrams, and memory-based imagery—not only supports narrative immersion but also deepens emotional engagement with the audience. The use of niche AI tools like Kakashi, as explored in one of Uketsu's most-viewed videos, reveals how personalized and emotionally resonant visuals can amplify horror storytelling. Furthermore, the findings highlight the importance of balancing human creativity with AI assistance to maintain originality and ethical integrity in digital content creation. While AI tools offer efficiency and personalization, creators must navigate challenges such as potential loss of artistic authenticity and overdependence on automated systems. Ultimately, this study offers insights into the evolving dynamics of narrative graphic design in the AI era, where technology serves not just as a tool but as an active participant in shaping audience experiences.